2011
DOI: 10.1166/jnn.2011.3048
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Processing of Hydrogen Titanate/Anatase-Titania Nanotubes and Their Application as Strong Dye-Adsorbents

Abstract: The nanotubes of pure hydrogen titanate and anatase-titania have been synthesized via hydrothermal treatment of as-received anatase-titania particles. The formation mechanism of anatase-titania nanotubes via hydrothermal has been discussed in detail in view of the finger-prints produced by characterizing the intermediate and end products using various microscopic and spectroscopic techniques such as scanning electron microscope, high-resolution transmission electron microscope, X-ray diffraction, Brunauer, Emm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…This has been mainly observed during the hydrothermal treatment of free-standing anatase-TiO 2 powder [3,4]. Interestingly, the morphology of final hydrothermal product observed here is not nanotubes, but consists of highly aggregated micro-spheres, Fig.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…This has been mainly observed during the hydrothermal treatment of free-standing anatase-TiO 2 powder [3,4]. Interestingly, the morphology of final hydrothermal product observed here is not nanotubes, but consists of highly aggregated micro-spheres, Fig.…”
Section: Resultsmentioning
confidence: 60%
“…For the latter method, various dyeadsorbents have been reported in the literature [2]. Recently, the nanotubes of hydrogen titanate (H 2 Ti n O 2n+1 ) and anatase-titania (TiO 2 ) processed via hydrothermal technique have received more attention due to their strong dye-adsorption property as a result of their higher specific surface-area and ability to exchange the cations in an aqueous solution under the dark-condition [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…It is, thus, unambiguously confirmed that when the nanocrystalline anatase-TiO 2 processed via the CH 3 COOH-modified solgel method is used as a precursor during the hydrothermal processing, the final hydrothermal products (nanotubes/ nanoplates) also have the highly crystalline anatasestructure irrespective of the amount of Ag-doping. Since several investigations have already reported the formation of nanotubes of hydrogen titanate when the anatase-TiO 2 is used as a precursor [31][32][33][34]47], the formation of nanotubes/nanoplates of anatase-TiO 2 is striking and attributed here to the effect of precursor-modification due to its processing via the CH 3 COOH-modified sol-gel method.…”
Section: -( O )mentioning
confidence: 83%
“…However, as described below during the hydrothermal processing, since the mechanism of formation of nanotubes/nanoplates involves an exfoliation of Na 2 Ti 3 O 7 nanosheets, the entrapped-CH 3 COO -anions are likely to be exposed on the surface of these nanosheets which then play a major role during the first washing-cycle resulting in the operation of as-proposed double ionexchange mechanism. The mechanism of formation of hydrogen titanate nanotubes/nanoplates via the hydrothermal technique using an unmodified anatase-TiO 2 precursor has been described in detail elsewhere by us [31,45] and others [43,44] which is also shown here in the Scheme 1a. In short, the hydrothermal treatment of anatase-TiO 2 under the autoclave conditions, in a highly alkaline solution, results in the formation of blocks of sodium titanate (Na 2 Ti 3 O 7 ) phase which has a layered-structure.…”
Section: -( O )mentioning
confidence: 94%
See 1 more Smart Citation